Groups with finiteness conditions on some subgroup systems: a contemporary stage - Dixon, M.R.; Subbotin, I.Ya. (Algebra and Discrete Mathematics, 2009)
This paper gives a brief historical survey of results in which certain systems of subgroups of a group satisfy various finiteness conditions.